(untitled) (Journal of Geography and Environmental Management, 2019)
The article discusses the current trends in the development of higher education in the specialty «Ecology». At present, society acquires an information status, for which information and knowledge become key. In accordance with this, the paradigm of education also changes. Modernization of the education and science system in Kazakhstan implies accessibility to each quality education, the opportunity to acquire new professional skills in college and university, and develop research and creative competences. For higher eecological education, the most relevant is the formation of a student’s culture of making environmentally appropriate practical solutions, experience of personal participation in solving environmental problems in order to improve the quality of the environment. At the same time, ecological competence as a developing personal property can and should become an indicator of the level of formation of egocentric ecological consciousness. The article presents practical experience in creating the educational program «Ecology» in English in the specialty 5B060800 – «Ecology».